THЕ DEVELOPMENT OF SCIENTIFIC AND ETHICAL THOUGHT IN CENTRAL ASIA DURING THE IX -XII CENTURIES (Scientific journal of the Fergana State University, 2026)
The article analyzes the scientific and ethical thought and its development in Central Asia during the 9th–12th centuries, as well as the social and cultural changes that occurred in the region. It highlights the works of thinkers who made an invaluable contribution to the development of spiritual and moral culture among the peoples of the Near and Middle East.